Analisis Fiqh Muamalah terhadap Praktik Produk Bundling: Studi Kasus Jual Beli Paket Pakaian pada Toko seltic_id - Affan Fadly Dawami; Imelda Aulia Suci; Muhammad Naufal Is Adurrofiq; Jaenudin J; Dian Herdiana (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
The phenomenon of bundling, which is the combination of several products in a single sales package at a combined price, has become a widely used marketing strategy in modern e-commerce. However, this practice raises questions about the validity of the contract and its compliance with sharia principles, particularly in relation to the elements of clarity, fairness, and willingness of the transacting parties. This study uses a legal-empirical approach by examining the implementation of bundling at the Seltic_ID store through direct observation and analysis of DSN-MUI fatwas No. 111 and 112 of 2017. The results show that the bundling system implemented has fulfilled the principles of fiqh muamalah because it is carried out transparently, fairly, and on the basis of mutual consent (an tarÄá¸in minkum). The seller provides clarity regarding product specifications, prices, and purchase options, thereby avoiding elements of gharar, tadlis, and maysir. Thus, the bundling practice at the Seltic_ID store is declared valid and in accordance with Islamic law principles and reflects the application of fiqh muamalah that is adaptive to the development of the digital economy